Incidence, severity, aetiology and prevention of sports injuries - van Mechelen, W.; Hlobil, H.; Kemper, H. C. G. (Sports Medicine, 1992)
Notwithstanding the healthy influence of sporting activities on risk factors, in particular those of cardiovascular disease, it is becoming increasingly apparent that sports can present a danger to health in the form of sports injuries. The extent of the sports injury problem calls for preventative action based on the results of epidemiological research. For the interpretation of these facts uniform definitions are needed and limitations of research designs should be known. Measures to prevent sports injuries form part of what is called the `sequence of prevention`. Firstly the extent of the sports injury problem must be identified and described. Secondly the factors and mechanisms which play a part in the occurrence of sports injuries have to be identified. The third step is to introduce measures that are likely to reduce the future risk and/or severity of sports injuries. This measure should be based on the aetiological factors and the mechanism as identified in the second step. Finally the effect of the measures must be evaluated by repeating the first step.